2012
DOI: 10.33585/cmy.64102
|View full text |Cite
|
Sign up to set email alerts
|

Rigidoporus pouzarii, a new polypore species related to Rigidoporus crocatus.

Abstract: The new polypore Rigidoporus pouzarii Vampola et Vlasák is described, occurring in alluvial forests, forming annual resupinate fruitbodies on lying dead stems of hardwoods, mostly Alnus species. In Europe, the species has been probably misidentified as R. crocatus, a closely related species differing by perennial, multi-layered fruitbodies and occurrence in old-growth mountain forests, preferentially on logs of Abies alba. Diagnostic features of both species are discussed and DNA sequences are also added. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 7 publications
(3 reference statements)
0
3
0
Order By: Relevance
“…Karst., but this similarity is evidently of only a superficial character. Many taxa had been described in Rigidoporus according to morphology (Ryvarden, 1972a;Ryvarden, 1972b;Ryvarden, 1983;Dai, 1998;Nuñez and Ryvarden, 1999;Buchanan and Ryvarden, 2000;Nuñez et al, 2001;Vampola and Vlasaḱ, 2012;Ryvarden, 2015), but phylogenetic studies demonstrated that they should be classified into Physisporinus belonging to Polyporales . revealed that Rigidoporus belongs to Hymenochaetales Oberw., and Oxyporus was considered as a synonym of Rigidoporus.…”
Section: Introductionmentioning
confidence: 99%
“…Karst., but this similarity is evidently of only a superficial character. Many taxa had been described in Rigidoporus according to morphology (Ryvarden, 1972a;Ryvarden, 1972b;Ryvarden, 1983;Dai, 1998;Nuñez and Ryvarden, 1999;Buchanan and Ryvarden, 2000;Nuñez et al, 2001;Vampola and Vlasaḱ, 2012;Ryvarden, 2015), but phylogenetic studies demonstrated that they should be classified into Physisporinus belonging to Polyporales . revealed that Rigidoporus belongs to Hymenochaetales Oberw., and Oxyporus was considered as a synonym of Rigidoporus.…”
Section: Introductionmentioning
confidence: 99%
“…Karst., but this similarity is evidently of only a superficial character. Many taxa had been described in Rigidoporus according to morphology (Ryvarden, 1972a;Ryvarden, 1972b;Ryvarden, 1983;Dai, 1998;Nuñez and Ryvarden, 1999;Buchanan and Ryvarden, 2000;Nuñez et al, 2001;Vampola and Vlasaḱ, 2012;Ryvarden, 2015), but phylogenetic studies demonstrated that they should be classified into Physisporinus belonging to Polyporales (Wu et al, 2017). Wu et al (2017) revealed that Rigidoporus belongs to Hymenochaetales Oberw., and Oxyporus was considered as a synonym of Rigidoporus.…”
mentioning
confidence: 99%
“…Ryvarden (Ryvarden, 1972;Ryvarden & Johansen, 1980); P. pouzarii (Vampola & Vlasák) F. Wu, Jia J. Chen & Y.C. Dai, formerly R. pouzarii Vampola & Vlasák (Vampola & Vlasák, 2012)] and have pore surfaces with vivid colors when fresh [e.g., P. lavendulus F. Wu, Jia J. Chen & Y.C. Dai (Wu et al, 2017); P. roseus Jia J. Chen & Y.C.…”
mentioning
confidence: 99%